PERBANDINGAN KONDUKTIVITASTEMBAGA, BAJA DAN ALUMINIUM - Mulyanto, Arif (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2011)
The heat transfer is important in engineering field and aspects of the life. Many equipment was made by using principles of the heat transfer, like: the oven, iron, the car machine, the muffler, the room cooler et cetera. The principle of the work in the research, there was the heat source at the upper side and the sink (heat remover) at the bottom side so that the temperature different ( was significant) along metal that was tested. The heat source from the electric heater,the object the test togethered with his heater all was isolated. The test object consisted aluminum with 20 mm2 cross section area, the steel and copper have 10 mm2 cross section area. The results that that the conductivity of copper was biggest were followed with aluminum and finally the steel.